International online survey: female ejaculation has a positive impact on women's and their partners' sexual lives. (25th January 2013) - Wimpissinger, Florian; Springer, Christopher; Stackl, Walter
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Genital secretions during female orgasm (female ejaculation) have been a matter of controversy for centuries. Scientific work on this essential part of female sexual function has been able to differentiate between female ejaculation, urinary incontinence and vaginal transudate. According to earlier studies, less than 50% of women actually do ejaculate during sexual stimulation. Few affected women discuss female ejaculation with their physician – partly because of its physiological nature, partly through embarrassment. To gain knowledge on the characteristics of female ejaculation and its impact on women's sexual lives, an online questionnaire has been designed and published internationally. In this way, data from 320 women who perceive ejaculation could be acquired. Most women and their partners perceive female ejaculation as an enrichment of their sexual lives. Objective To study characteristics of female ejaculation as perceived by healthy women. To evaluate whether fluid emission during sexual activity has an impact on women's or their partners' sexual lives. Materials and Methods An online questionnaire consisting of 23 questions addressing the participants' characteristics, aspects of perceived female ejaculation, and its impact on women's and their partners' lives was published internationally on various online platforms. Results Over a period of 18 months, 320 women from all over the world were included in the study (excluding women below the age of 18 years and double entries). The women's mean age was 34.1 years (±11.1) and their mean age at first ejaculation was 25.4 years. Most women ejaculate a few times a week. The volume of ejaculation is approximately 2 oz (29.1%), and the fluid is usually clear as water (83.1%). For most women (78.8%) and their partners (90.0%), female ejaculation is an enrichment of their sexual lives, whereas 14 women (4.4%) stated that their partners were unaware of their potential ejaculation. Conclusions Perceived female ejaculation – and its onset – occurs in women of all ages. Most women who ejaculate do so on a regular basis. Female ejaculation is an enrichment of the sexual lives of women as well as their partners.